Prenatal, Perinatal and Postnatal Exposures and Clinical Factors of Food Allergy Prevention: A Review for the First 1000 Days of Life from the SIAIP Primary and Secondary Prevention of Allergic Diseases Commission - Angela Klain; Salvatore Cascone; Carolina Grella; Valentina Cattivera; Cecilia Fabiano; Francesca Galletta; Sara Manti; Antonio Andrea Senatore; Amelia Licari; Michele Miraglia del Giudice; Gian Luigi Marseglia; Cristiana Indolfi (Nutrients, 2026)
Background/Objectives: Food allergy prevention is no longer understood as the simple avoidance of allergenic foods. The first 1000 days (from conception to, approximately, 24 months of age) include prenatal, perinatal and postnatal windows in which diet, epithelial barrier integrity, microbial ecology, immune maturation and family-level implementation interact. This narrative review was developed as a Commission-proposed SIAIP-oriented clinical framework, rather than a formal guideline or consensus statement. Evidence from guidelines, systematic reviews, randomised trials, birth cohorts and mechanistic studies was organised by developmental window and interpreted according to endpoint validity, confounding, feasibility and clinical readiness. Prenatal factors include maternal allergen non-avoidance, whole-diet quality, micronutrient and fatty acid status, antibiotic exposure, environmental context and maternal microbiome. Perinatal factors include mode of delivery, intrapartum and neonatal antibiotics, gestational maturity, early colonisation, breastfeeding initiation and routine vaccination. Postnatal factors include eczema, skin barrier inflammation, the timing and regularity of allergen introduction, breastfeeding management, infant diet diversity, siblings, daycare, pets, smoke and pollution, physical activity and equitable implementation. The strongest actionable evidence remains eczema-linked risk recognition and timely, sustained oral exposure to peanut and well-cooked egg. Maternal and environmental factors are clinically important, but many are contextual rather than prescriptive; they should guide non-restrictive, non-blaming counselling rather than deterministic risk labelling.